PERAN TEKNOLOGI DIGITAL DALAM PENGEMBANGAN KARIR GENERASI MILENIAL - Bela, Bela; Wibowo, Cokorda Agung; Anhara, Awan (National Conference on Applied Business, Education, & Technology (NCABET), 2024)
This study aims to analyze the implementation of technology in career planning in the digital era in examining its opportunities and challenges and the implementation of technology in career planning in the digital era, offering significant opportunities and challenges. In the digital age, technology has become an integral part of various aspects of life, including in career planning. Technology can help individuals make more informed and effective decisions in planning their careers. However, the implementation of technology can also pose challenges such as how technology can be used effectively and how technology can be used effectively and how individuals can utilize technology to improve their quality of life and career. The purpose of this study is to find out and analyze the opportunities and challenges of technology implementation in career planning in the digital era. The research methodology carried out by this researcher uses a qualitative approach with a descriptive method. The data collection technique was carried out using literature study techniques that referred to several sources such as journals, and other literature reviews. The results of this study show that technology can help individuals make more informed and effective decisions in planning their careers. However, the implementation of technology can also pose challenges, such as how technology can be used effectively and how individuals can utilize technology to improve their quality of life and career